(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
Teacher motivation relates to the reasons associated with individual intrinsic value for choosing to teach and maintain teaching. This research aimed at finding out the honorary teacher motivation and orientation in teaching English at SMP IT Nurul Fikri Makassar. The honorary English teachers was the informants of this study. This research used the qualitative method with a description approach for details. The data was taken by interview and observation in school. It was found that the honorary teacher’s motivations of teaching are love teaching, hope for a great future career, dedication, getting experience, and being a glorious person. The honorary teacher admits that they are less prosperous, but they continue to carry out his profession for these reasons. They hope that what they did while serving material in the class can improve them and their students.